Overview of Clinical Cytogenetics. (1st April 2016) - Gonzales, Patrick R.; Carroll, Andrew J.; Korf, Bruce R.
Abstract: Chromosome analysis is one of the first approaches to genetic testing and remains a key component of genetic analysis of constitutional and somatic genetic disorders. Numerical or unbalanced structural chromosome abnormalities usually lead to multiple congenital anomalies. Sometimes these are compatible with live birth, usually resulting in severe cognitive and physical handicaps; other times they result in miscarriage or stillbirth. Chromosome rearrangements also occur as somatic changes in malignancies. Identification of constitutional chromosomal anomalies (anomalies present in most or all cells of the body and/or the germline) can provide important information for genetic counseling. In this unit, we introduce chromosomal microarray analysis (CMA), which is a relatively recent addition to cytogenetic technologies, and has become the recommended first‐tier testing method for patients with developmental delay, intellectual disability, autism, and/or multiple congenital anomalies. We also discuss non‐invasive prenatal testing/screening (NIPTS), which uses circulating cell‐free fetal DNA (cfDNA) from maternal plasma to rapidly screen for autosomal and sex‐chromosome aneuploidies. Cytogenetic analysis of tumors is helpful in diagnosis and in monitoring the effects of treatment. The protocols in this chapter cover the clinical study of chromosomes in nonmalignant tissues. © 2016 by John Wiley & Sons, Inc.